The Post-War Reconstruction of Greece A History of Economic Stabilization and Development, 1944-1952 - Politakis, George (Palgrave Studies in Democracy, Innovation, and Entrepreneurship for Growth,, 2018)
The book presents the first comprehensive account of how economists, engineers and industrialists mapped out the economic future of Greece in the aftermath of civil war devastation. It documents the policy debate that took place among Greece and its sponsors about the future course of the economy, the required investment and their financing. Through historical narrative, archival sources and oral history, this book offers a better understanding of the achievements proclaimed by many economists as an "economic miracle".